Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.21203/rs.3.rs-341528/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diffusion modeling reveals effects of multiple release sites and human activity on a recolonizing apex predator

Abstract: Background: Reintroducing predators is a promising conservation tool to help remedy human-caused ecosystem changes. However, the growth and spread of a reintroduced population is a spatiotemporal process that is driven by a suite of factors, such as habitat change, human activity, and prey availability. Sea otters (Enhydra lutris) are apex predators of nearshore marine ecosystems that had declined nearly to extinction across much of their range by the early 20th century. In Southeast Alaska, which is comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 55 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…Several methods for defining range extent have been used for sea otter populations (Bowlby et al 1988, Lubina and Levin 1988, Hatfield et al 2019), and we estimated sea otter range extent in Washington and observed rates of range expansion using a variety of methods (Table , available in Supporting Information; −0.8 km/year to 2.24 km/year). All of these methods resulted in lower estimated rates of range expansion for sea otters in Washington than typical rates from other studies (2–6 km/year; Lubina and Levin 1988, Tinker et al 2008 b , Williams et al 2019, Eisaguirre et al 2021), and each method produced very different estimates for the same range expansion front (north or east front and south front). We lacked reliable estimates of rates of range expansion for sea otters in Washington, so we used a diffusion approximation to simulate future population growth and range expansion under a range of biologically realistic population parameters (including rate of range expansion) and used these forward projections as the basis of a sensitivity analysis to explore how variation in population parameters would influence predictions of future population growth.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Several methods for defining range extent have been used for sea otter populations (Bowlby et al 1988, Lubina and Levin 1988, Hatfield et al 2019), and we estimated sea otter range extent in Washington and observed rates of range expansion using a variety of methods (Table , available in Supporting Information; −0.8 km/year to 2.24 km/year). All of these methods resulted in lower estimated rates of range expansion for sea otters in Washington than typical rates from other studies (2–6 km/year; Lubina and Levin 1988, Tinker et al 2008 b , Williams et al 2019, Eisaguirre et al 2021), and each method produced very different estimates for the same range expansion front (north or east front and south front). We lacked reliable estimates of rates of range expansion for sea otters in Washington, so we used a diffusion approximation to simulate future population growth and range expansion under a range of biologically realistic population parameters (including rate of range expansion) and used these forward projections as the basis of a sensitivity analysis to explore how variation in population parameters would influence predictions of future population growth.…”
Section: Discussionmentioning
confidence: 75%
“…We parametrized v separately for southward and eastward range expansion, thereby allowing for differing rates of range expansion at either end of the range, consistent with previously observed patterns of range expansion (Figure 1). We set maximum v values to 5 km/year, comparable with previous studies (3‒6 km/year; Lubina and Levin 1988, Tinker et al 2008 b , Williams et al 2019, Eisaguirre et al 2021). To allow for the possibility of range expansion stopping, we set the minimum v values to zero.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…One of the most studied cases is the range expansion of the sea otter ( Enhydra lutria ) across North Pacific following translocations (Tinker et al, 2008). Mechanistic models of ecological diffusion have been used to estimate spatiotemporal changes in occupancy and abundance of this gregarious carnivore from counts of individuals (Eisaguirre et al, 2021; Lubina & Levin, 1988; Williams et al, 2017, 2019).…”
Section: Introductionmentioning
confidence: 99%